2007
DOI: 10.1167/iovs.06-1285
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Orientation of Zernike Terms in Patients with Keratoconus

Abstract: In addition to the larger amount of trefoil, coma, tetrafoil, and secondary astigmatism, keratoconic eyes tend to have a reverse coma pattern and reverse trefoil aberrations compared with normal eyes. Although RGP lenses correct the irregular astigmatism, smaller comet-like retinal images in the opposite direction remain due to residual vertical coma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
123
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(144 citation statements)
references
References 30 publications
14
123
0
7
Order By: Relevance
“…Ao contrário, as lentes gelatinosas tenderiam a preservar as aberrações de alta ordem dependendo de seu grau de complacência com a superfície anterior da córnea (9) . Estudo realizado na Universidade de Osaka, Japão, demonstrou que em pacientes com ceratocone, o uso de lentes rígidas gás permeáveis causa redução significante das aberrações de alta ordem (10) . Durante estudo prospectivo em olhos de pacientes altamente sintomáticos que fizeram cirurgia refrativa, foram adaptadas LCRGP semi-esclerais.…”
Section: Discussionunclassified
“…Ao contrário, as lentes gelatinosas tenderiam a preservar as aberrações de alta ordem dependendo de seu grau de complacência com a superfície anterior da córnea (9) . Estudo realizado na Universidade de Osaka, Japão, demonstrou que em pacientes com ceratocone, o uso de lentes rígidas gás permeáveis causa redução significante das aberrações de alta ordem (10) . Durante estudo prospectivo em olhos de pacientes altamente sintomáticos que fizeram cirurgia refrativa, foram adaptadas LCRGP semi-esclerais.…”
Section: Discussionunclassified
“…However, recent studies of HOAs in patients with keratoconus have revealed a problem whereby the residual irregular astigmatism derived from the posterior surface of the cornea causes vision quality deterioration while wearing RGPCLs. 4,5 Anxiety and disruption of daily life occur because of the psychological pressure of tolerating the foreign body sensation and the inability to use the lenses when playing sports. 6,7 In addition, the risk of corneal warpage caused by mechanical stress on the cornea, the relatively higher cost associated with processing and manufacturing of the contact lenses, and the fact that prescription is generally difficult are potential problems that are specific to RGPCLs.…”
mentioning
confidence: 99%
“…4,11,12 Most of these eyes have vertical coma where the wavefront is fast in the superior portion and slow in the inferior portion due to a superior-inferior asymmetry of the shape of the cornea in eyes with keratoconus. 4 Therefore, like standard clothing sizes (small, medium, large) or current toric SCLs, it might be possible to create semicustomized SCLs for keratoconus with a standardized coma design (consisting of the standardized amount and a particular axis of coma) that could be easily and inexpensively prescribed as standardized sets of lenses.…”
mentioning
confidence: 99%
“…A aberrometria ocular tem seu papel destacado em casos de ceratocone para diagnóstico (57,(63)(64)(65)(66) , estadiamento (67) , e avaliação do tratamento realizado (65,(68)(69)(70)(71) . O presente estudo pretende avaliar se os dados objetivos com a aberrometria ocular total podem auxiliar na refratometria manifesta, de modo a proporcionar melhor acuidade visual corrigida com óculos (AVc).…”
unclassified